(untitled) (KULT_online, 2015)
Farzad Boobani’s study Orientalist Imaginings. Representations of Persia in Nineteenth-Century English Literature provides a detailed examination of the topic. In a number of close-reading analyses the author shows his deep knowledge and understanding of literature. Moreover, the study displays the complex relations between different interests and representations of the Orient in English literature.